Comparison of SARS-CoV-2 seroconversion in children with chronic diseases with healthy children and adults during the first waves of the COVID-19 pandemic - Hoste, Levi; Prytula, Agnieszka; Dehoorne, Jo; De Bruyne, Ruth; Van Biervliet, Stephanie; De Waele, Kathleen; Maes, Evelyn; Bordon, Victoria; Vanlander, Arnaud; Claes, Karlien; Vande Walle, Johan; Schelstraete, Petra; et al. (Frontiers in Pediatrics, 2023)
Background Infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is clinically diverse with low susceptibility for severe coronavirus disease 2019 (COVID-19) in children. Children with chronic diseases are potentially at increased risk. Methods We performed a prospective surveillance study with longitudinal serum SARS-CoV-2 anti-nucleocapsid antibody quantification and questionnaires in pediatric tertiary care patients during the first waves of the COVID pandemic (November 2020-September 2021). Results were compared to healthy children and adults from the same geographic area. Results We obtained 525 samples from 362 patients (M/F 1.3:1; median age 11.1y), comprising children with immune suppressive or modulating drugs (32.9%), inborn errors of immunity (23.5%), type 1 diabetes mellitus (15.2%), and rheumatic diseases (11.9%). Fifty-one (9.7%) samples were seropositive among 37/351 children (10.5%). Seropositivity increased from 5.8% in November-December 2020 to 21.6% in July-September 2021. Compared to adults, longitudinal analysis revealed reduced seroprevalence but similar kinetics as in children from the same country. Demographic or social variables and disease characteristics did not correlate with seropositivity. Being obese and household contacts with COVID-19 significantly increased odds for infection. The majority of seropositive patients had mild symptoms (21/37). One third were asymptomatic and/or not aware having COVID-19 (10/37). Four patients (4/37) needed hospitalization, with good clinical outcomes. Conclusions Although harboring a chronic disease, we observed a low SARS-CoV-2 incidence in a cohort of pediatric tertiary care patients, comparable with healthy children during the first year of the pandemic. Infection was mostly associated with mild symptoms.